Progress in Combined Liver–lung Transplantation at a Single Center. Issue 5 (20th April 2023) - Connor, Ashton A.; Huang, Howard J.; Mobley, Constance M.; Graviss, Edward A.; Nguyen, Duc T.; Goodarzi, Ahmad; Saharia, Ashish; Yau, Simon; Hobeika, Mark J.; Suarez, Erik E.; Moaddab, Mozhgon; Brombosz, Elizabeth W.; et al.
Abstract : Background: Combined liver–lung transplantation is an uncommon, although vital, procedure for patients with simultaneous end-stage lung and liver disease. The utility of lung–liver transplant has been questioned because of initial poor survival outcomes, particularly when compared with liver-alone transplant recipients. Methods: A single-center, retrospective review of the medical records of 19 adult lung–liver transplant recipients was conducted, comparing early recipients (2009–2014) with a recent cohort (2015–2021). Patients were also compared with the center's single lung or liver transplant recipients. Results: Recent lung–liver recipients were older ( P = 0.004), had a higher body mass index ( P = 0.03), and were less likely to have ascites ( P = 0.02), reflecting changes in the etiologies of lung and liver disease. Liver cold ischemia time was longer in the modern cohort ( P = 0.004), and patients had a longer posttransplant length of hospitalization ( P = 0.048). Overall survival was not statistically different between the 2 eras studied ( P = 0.61), although 1-y survival was higher in the more recent group (90.9% versus 62.5%). Overall survival after lung–liver transplant was equivalent to lung-alone recipients and was significantly lower than liver-alone recipients (5-y survival: 52%, 51%, and 75%, respectively). Lung–liver recipient mortality was primarily driven by deaths within 6 mo of transplant due to infection and sepsis. Graft failure was not significantly different (liver: P = 0.06; lung: P = 0.74). Conclusions: The severity of illness in lung–liver recipients combined with the infrequency of the procedure supports its continued use. However, particular attention should be paid to patient selection, immunosuppression, and prophylaxis against infection to ensure proper utilization of scarce donor organs.